Exploring Tapestry Materials in Men’s Denim Jacket Design - Nada Asy Syifa’; Hesti Yanuaristi; Nadila Yuniar; Citra Marsyayu Fita Cherry; Difla Naila Zulfa; Irmayanti Irmayanti; Saifudin Aulya Akhsan (Jurnal Penelitian Pendidikan, 2026)
The fashion industry faces increasing pressure to adopt sustainable practices due to the growing volume of textile waste generated by fast fashion consumption. This study explores the application of tapestry materials as an innovative design element in men's denim jackets through an upcycling approach. The research aims to examine the aesthetic, functional, and sustainable potential of combining reclaimed denim with tapestry textiles in contemporary ready-to-wear menswear. A practice-based design research method was employed, including material exploration, concept development, design experimentation, and prototype creation. Tapestry materials were selected for their rich textures and distinctive patterns, while patchwork construction, fabric manipulation, and decorative stitching techniques were applied to integrate the materials into denim jacket designs. The results demonstrate that tapestry materials significantly enhance the visual appeal of denim jackets by creating unique focal points, increasing product value, and strengthening product individuality. Furthermore, the combination of recycled denim and tapestry textiles supports circular fashion principles by extending material life cycles and reducing textile waste. This study concludes that the integration of tapestry materials into denim jackets offers an innovative and sustainable design strategy that successfully combines environmental responsibility, functionality, and contemporary aesthetics in menswear.